Detection of PMU spoofing in power grid based on phasor measurement analysis. Issue 9 (23rd February 2018) - Yasinzadeh, Mohammad; Akhbari, Mahdi
Abstract : In some recent articles, the vulnerability of phasor measurement unit (PMU) to the time synchronisation attack by spoofing its global positioning system (GPS) has been highlighted as a threat to power grid protection, control and monitoring system. Having spoofed PMU GPS signals, one can manipulate the measurements and inject bad data to power grid protection and monitoring system. The existing anti‐spoofing methods are all based on GPS signal analysis. The mentioned methods are just able to detect spoofing without any data refinement as the data of power grid has not been practically used in calculations. Furthermore, some of these methods lose their certainty in noisy and harsh environments due to low power of GPS signals. A novel anti‐spoofing algorithm has been proposed based on power grid infrastructures which can join to any of the existing anti‐spoofing algorithm to empower spoofing detection process. The proposed algorithm adopts phasor measurement analysis and state estimation methods to detect spoofing. The composite of this algorithm with any of the existing algorithms will not only cover the probable malfunctioning in spoofing detection but also be able to refine counterfeit measurements.